2022
DOI: 10.1007/s11033-022-07121-w
|View full text |Cite
|
Sign up to set email alerts
|

miR-126 ameliorates multiple organ dysfunction in septic rats by regulating the differentiation of Th17/Treg

Abstract: Background The most common cause of death in sepsis is MODS. We hope that miR-126 can regulate the differentiation of Th17/Treg, reduce the infiltration of inflammatory factors in peripheral blood and various organs and tissues, and improve organ function and prognosis in sepsis. Methods and results Septic rat model was established by cecal perforation and ligation. miR-126 mimic and inhibitor were used to intervene sepsis. The experimental results showed that miR-126 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…21 T cell differentiation into Th1 cell and Th17 cell plays an important role in the pathogenesis role in sepsis. 25,26 For instance, one study shows that Th17 cells induced immunosuppression plays a vital role in sepsis. 25 In our study, we found that lnc-GAS5 negatively correlated with Th17 cell and its secreted inflammatory cytokine (IL-17A), also However, this hypothesis needed further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 T cell differentiation into Th1 cell and Th17 cell plays an important role in the pathogenesis role in sepsis. 25,26 For instance, one study shows that Th17 cells induced immunosuppression plays a vital role in sepsis. 25 In our study, we found that lnc-GAS5 negatively correlated with Th17 cell and its secreted inflammatory cytokine (IL-17A), also However, this hypothesis needed further exploration.…”
Section: Discussionmentioning
confidence: 99%
“… 21 T cell differentiation into Th1 cell and Th17 cell plays an important role in the pathogenesis role in sepsis. 25 , 26 For instance, one study shows that Th17 cells induced immunosuppression plays a vital role in sepsis. 25 In our study, we found that lnc‐GAS5 negatively correlated with Th17 cell and its secreted inflammatory cytokine (IL‐17A), also it negatively associated with CRP which might be explained that (1) lnc‐GAS5 inhibited the T cell differentiation into Th17 cells, therefore it negatively associated with Th17 cells and IL‐17A in sepsis, and (2) lnc‐GAS5 restrained the inflammatory response, hence, it negatively correlated with CRP level in sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological evaluation criteria were as follows: edema, structural changes, and inflammatory cell infiltration of various organ lesions, from light to heavy, were divided into four degrees corresponding to 0–4 points. (0, no or very slight damage; 1, mild injury; 2, moderate injury; 3, severe injury; and 4, very severe damage [ 65 ] ). The final score was the sum of the scores of each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies suggest that EV caspase-1 activity can induce EC injury and that sepsis-induced pyroptosis of monocytes and ECs can release caspase-1 containing EVs ( 15 18 ). Conversely, EV miR-126 has been shown to stabilize the endothelium in sepsis while modulating sepsis-related organ failure ( 19 22 ). However, the potential role of circulating total or cell-specific EVs in septic patients and their association with sepsis outcomes such as organ failure and mortality are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%